Staffing dalam Administrasi Pendidikan - Hilda Melani Purba; Pramudia Ananda; Siti Fadilla (Universitas Maritim AMNI Semarang, 2024)
Staffing in educational administration is a structural management process that aims to obtain effective employees to fill vacant positions in educational institutions. This function involves attracting, selecting, developing and using human resources to achieve organizational goals effectively and efficiently. In educational institutions, staffing is very important to ensure that employees are placed in positions that match their competencies, so that organizational goals can be achieved more easily. In its implementation, staffing must be guided by clear rules and pre-determined prerequisites, as well as taking into account factors such as the wishes of the organization, the wishes of the workforce, expiring work contracts, labor regulations, retirement and death. Thus, staffing can help improve employee performance and achieve educational goals more effectively and efficiently.